Aldose reductase inhibitory compounds from extracts of Dipsacus asper - Koo, Dong Chil; Baek, So Yoon; Jung, Sang Hoon; Shim, Sang Hee (KOREAN SOC BIOTECHNOLOGY & BIOENGINEERING, 2013)
Amethanolic extract of Dipsacus asper, having anti-diabetic activity, was examined as a possible aldose reductase (ALR2) inhibitor, a key enzyme involved in diabetic complications. Bioactivity guided fractionation led to the isolation of ten compounds, ursolic acid (1), oleanolic acid-3-O-alpha-L-arabinopyranoside (2), daucosterol (3), hederagenin-3-O-alpha-L-arabinopyranoside (4), sweroside(5), caffeic acid (6), esculetin (7), protocatechualdehyde (8), loganin (9), and vanilic acid (10) from the ethyl acetate fraction of D. asper methanol extract. Among them, compounds 4, 6, 7, and 8 exhibited inhibitory effects on aldose reductase, with IC50 values of 23.70, 16.71, 34.36, and 21.81 mu M, respectively. This is the first report on the isolation of these compounds from D. asper, and the ALR2 inhibitory activity of hederagenin-3-O-alpha-L-arabinopyranoside. These results suggest the successful use of the extract of D. asper for ameliorating diabetic complications.
Keywords: STRUCTURAL REQUIREMENTS; DIABETIC-RATS; GLYCATION; LENS; FLAVONOIDS; ACID